Melhoramento de sensores magnetostrictivos de deformação - Dalponte, Alessandro (My University, 2017)
Magnetic amorphous ribbons have a great variety of sensorial applications due to their magnetic properties. The possibility of being remotely queried allows their application in cases where sensors with wired connections present a physical limitation. The capability of acquiring a transverse magnetic anisotropy through thermal treatments, under applied magnetic field and/or stress, is what makes these materials attractive for application in magnetostrictive strain-gauges. The materials studied in this work, Metglas 2826MB3, Yeke 1k501, Yeke 1k501a, Vitrovac 7600, Vitroperm 800 and a commercial EAS Tags, presented magnetization curves with characteristics of materials with reduced transverse magnetic anisotropy. This was the motivation to carry out thermomagnetic treatments. The treatments were carried out under a magnetic field of approximately 500 Oe, using temperatures of 235, 275, 315 and 350˚C, for periods of 15, 30 and 60 minutes, in a home-made oven. The treatments resulted in considerable improvements on the shape of the ΔE curves, making them more asymmetric and increasing the frequency variations that these materials can present. The treatments also resulted in linear M-H curves, with constant magnetic susceptibility until saturation. A system for the application of stresses up to 30 MPa on the samples was built. ΔE curves with greater asymmetry for the pair resonator transducer (components of the strain-gauge) allowed a greater resonance frequency variation response of the sensor during strain tests. In the best case, a frequency variation above 5 kHz was detected for deformations of approximately 260 ppm, when the pair resonator transducer made of thermomagneticaly treated Metglas 2826MB3 was used. The measurements of the ΔE curves of a treated Metglas 2826MB3 ribbon, placed over 1010 steel substrates, soft magnetic material, showed that they were still detectable. However, their form was altered due to the magnetic interaction with the steel. Simulations made using the software FEMM, helped to understand the observed phenomena during the strain tests and the interaction between the ribbon and the soft magnetic substrates.
Fitas magnéticas amorfas vêm demonstrando uma ampla variedade de aplicações sensoriais devido às suas propriedades magnéticas. A capacidade de serem interrogadas remotamente permite sua aplicação em locais onde limitações físicas impedem o uso de sensores com conexões cabeadas. A capacidade de adquirirem uma anisotropia magnética transversal através de tratamentos térmicos, sob campo magnético e/ou tensão, é o que torna esses materiais atraentes para a aplicação em sensores magnetostrictivos de deformação com acesso remoto. Os materiais avaliados neste trabalho, Metglas 2826MB3, Yeke 1k501, Yeke 1k501a, Vitrovac 7600, Vitroperm 800 e as fitas de EAS Tags, apresentavam curvas de magnetização características de materiais que não possuem uma anisotropia magnética transversal. Isto serviu de motivação para a realização de tratamentos termomagnéticos. Os tratamentos foram realizados sob campo magnético transversal de aproximadamente 500 Oe e nas temperaturas de 235, 275, 315 e 350˚C por tempos de 15, 30 e 60 minutos, com um forno construído em laboratório. Isto resultou em melhorias consideráveis na forma de suas curvas ΔE, tornando-as mais assimétricas e aumentando as variações de frequência que estes materiais podem apresentar. Os tratamentos resultaram também em curvas M-H lineares, susceptibilidade magnética constante até a saturação. Foi construída uma bancada para aplicação de tensões de até 30 MPa nas amostras. A maior assimetria das curvas ΔE para o par ressonador e transdutor (partes componentes do sensor de deformação) permitiu maior resposta de variação de frequência de ressonância do sensor durante testes de tração. No melhor dos casos, uma variação de frequência superior a 5 kHz foi detectada para deformações de aproximadamente 260 ppm, ao se utilizar um par ressonador e transdutor de Metglas 2826MB3 tratados termomagneticamente. Medindo-se as curvas ΔE de uma fita de Metglas 2826MB3, tratada, sobre substratos de aço 1010, material magneticamente mole, observou-se que as mesmas ainda estavam presentes. Porém, apresentam sua forma alterada devido à interação com aço. Simulações realizadas com o software FEMM, auxiliaram na compreensão de fenômenos ocorridos nos testes de deformação e na interação entre a fita e os substratos magnéticos moles.
Keywords: Fitas magnéticas; Sensoriamento remoto; Magnetismo; Magnetic tapes; Magnetism; Remote sensing